Atomic layer deposition of a ruthenium thin film using a precursor with enhanced reactivity. Issue 11 (12th March 2021) - Hwang, Jeong Min; Han, Seung-Min; Yang, Hanuel; Yeo, Seungmin; Lee, Seung-Hun; Park, Chan Woo; Kim, Gun Hwan; Park, Bo Keun; Byun, Younghun; Eom, Taeyong; Chung, Taek-Mo
Abstract : The incubation cycle free ALD Ru film was deposited using an open-coordinated structured Ru(ii ) precursor, Ru(η 5 -cycloheptadienyl)2 . Abstract : Ruthenium (Ru) thin films were grown via atomic layer deposition (ALD) using a novel Ru precursor with enhanced reactivity, namely Ru(η 5 -cycloheptadienyl)2 (Ru(chd)2 ) and O2 . Self-limiting growth during the Ru ALD process was achieved by varying the Ru precursor and O2 feeding times. Metallic Ru films with a low resistivity (10–16 μΩ cm) grew at deposition temperatures between 200 and 300 °C, where the growth per cycle (GPC) during Ru ALD was 0.2 to 0.4 Å cy −1 at 265 °C. The Ru incubation times were considerably shorter using the novel precursor (negligible on Pt and TiN, ∼22 cycles on SiO2 ) compared with those associated with Ru ALD using a high-valency Ru precursor and O2 . The characteristics of the Ru film were influenced by the substrate. Specifically, the Pt substrate gave rise to an amorphous film, while crystalline films were grown on the TiN and SiO2 substrates, where a high RuO x content resulted on the SiO2 substrate.